(untitled) (Marketing Journal, 2025)
This research paper analyzes international approaches to accounting and managing construction and renovation expenditures in public sector organizations, focusing on lifecycle costing of infrastructure assets, clear differentiation between capital and oper ational expenditures (CAPEX/OPEX), digital cost monitoring platforms, post -tender variation control, and value -for-money (CBA) assessment. Findings indicate that the integrated application of these mechanisms increases transparency of construction spending , mitigates budget overruns, and improves long - term management of public infrastructure. The study evaluates the applicability of global practices to Uzbekistan and concludes that the introduction of CAPEX/OPEX budgeting codes, real -time monitoring systems , a post -tender variation registry, and lifecycle cost passports can significantly enhance efficiency and accountability of construction and renovation expenditures in the public sector.